2019
DOI: 10.1111/mec.15018
|View full text |Cite
|
Sign up to set email alerts
|

Contrasting evolutionary histories in Neotropical birds: Divergence across an environmental barrier in South America

Abstract: Avian diversity in the Neotropics has been traditionally attributed to the effect of vicariant forces promoting speciation in allopatry. Recent studies have shown that phylogeographical patterns shared among codistributed species cannot be explained by a single vicariant event, as species responses to a common barrier depend on the biological attributes of each taxon. The open vegetation corridor (OVC) isolates Amazonia and the Andean forests from the Atlantic Forest, creating a notorious pattern of avian taxa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
29
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 24 publications
(31 citation statements)
references
References 96 publications
(164 reference statements)
1
29
1
Order By: Relevance
“…Interestingly, the belly of these two subspecies was the only plumage patch that showed both statistical and perceptual significant differences among all comparisons made (above). This difference in the plumage coloration of the belly adds to the deep genetic and vocal divergence between R. m. megacephalum and R. m. bolivianum reported by Lavinia et al (), and contrasts with the lack of morphological differentiation reported here.…”
Section: Discussioncontrasting
confidence: 65%
See 3 more Smart Citations
“…Interestingly, the belly of these two subspecies was the only plumage patch that showed both statistical and perceptual significant differences among all comparisons made (above). This difference in the plumage coloration of the belly adds to the deep genetic and vocal divergence between R. m. megacephalum and R. m. bolivianum reported by Lavinia et al (), and contrasts with the lack of morphological differentiation reported here.…”
Section: Discussioncontrasting
confidence: 65%
“…The Atlantic Forest could have been colonized from western Amazonia via elevated land bridges and forest corridors that connected the Andes to the Brazilian shields. Alternatively, the appearance of the open and dry environments that currently isolate the Amazonia from the Atlantic Forest could have disrupted a former continuous distribution of R. megacephalum (Lavinia et al for a more detailed discussion on this subject).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Th ese studies led to separate the hoopoe from Coraciiformes into other order and then in 2017, it has been jointed with the hornbills into Bucerotiformes order ( (Mayr, 2000;Gill & Donsker, 2017). Although, we were noticed that many molecular studies were concentrated on the phylogenetic relationships between bird species (Lavinia et al, 2019;Barreira et al, 2016;Lijtmaer et al, 2012;Campagna et al, 2012) but the study of avian cranio-mandibular system is still interesting subject (Demmel Ferreira et al, 2019;Zelenkov, 2017;Fabbri et al, 2017;Ni et al, 2017) to try understand the functional ecological classifi cation of bird species beside clarify some modifi cations that specifi c to each species ( species-specifi c feature).…”
Section: Introductionmentioning
confidence: 99%